Leave No One Behind? Analysing Sport Inclusion Policy‐Implementation for Persons With Disabilities in Ghana - Derrick Charway; Francis Asare; Allan Bennich Grønkjær (Social Inclusion)
Sport inclusion policies for persons with disabilities are prevalent in many countries; however, actual support in local communities is lacking or inadequately addressed. In this article, we analyse the implementation of sport inclusion policies and the extent to which they exclude or include disabled sport associations in Ghana’s District Sports Units. Using document analysis, focus group discussions, and semi‐structured interviews, we collected data from representatives of state and non‐state organisations, drawing theoretical insights from ableism and policy networks to analyse the implementation of sport inclusion policies. The findings reveal that despite inclusion provisions at the local level, the policy implementation process presents challenges for District Sports Units. These challenges include the lack of funding, conflicts among network actors, deliberate disregard, membership gaps, and the absence of an integrated programme for disabled sport associations. These findings further inform our understanding of collaborative alliances, local autonomy, and the implication of ableism for policy networks.